Work Training, Workplace Relationships, Workload and Job Performance - Niere (Mecon), Marvin Ian E.; Narsico, Lalaine O.; Narsico, Peter G. (Future Science / FSH-PH Publications, 2024)
This study explores the optimization of job performance by examining the interplay of work training, workplace relationships, and workload within the dynamic setting of a call center. The overarching goal is to gain a holistic understanding of how these three elements collectively contribute to fostering a positive impact on workforce productivity. Utilizing a descriptive survey method, the research employed a questionnaire to systematically collect data on the perceived positive effects associated with work training, workplace relationships, and workload on job performance. Following data collection, thorough analysis and interpretation were conducted to derive meaningful insights. To assess the significance of differences between the factors influencing job performance, a one-way ANOVA was applied. The study aimed to shed light on several key aspects, including the dynamics of the work environment concerning the identified factors affecting job performance, the levels of agreement among respondents regarding these factors, significant differences in responses, and implications for improvements. In conclusion, the study highlights that work training, workplace relationships, and workload positively influence job performance, as evidenced by responses from call center agents. However, it is noteworthy that all three factors were rated one level below the highest possible classification, underscoring the need for targeted interventions. Significant differences in ratings were identified among work training, workplace relationships, and workload. All three factors were considered for intervention, with a particular emphasis on workload, which received the lowest rating. This prioritization sets the groundwork for strategic improvements to elevate overall job performance in the call center environment.